Comment: Empathy as a Flexible and Fundamentally Interpersonal Phenomenon: Comment on "Why We Should Reject the Restrictive Isomorphic Matching Definition of Empathy". (July 2022) - Main, Alexandra
I strongly agree with the criticisms of the restrictive isomorphic matching (RIM) definition of empathy made by Murphy, Lilienfeld, and Algoe (2022), and largely agree with their conceptualization of empathy as a dynamic process best defined by its function. In this commentary, I extend this argument by emphasizing the relational, interpersonal aspects of empathy. It is my view that in order to understand the functions of empathy, we must take into account not only the internal experience of the individual empathizing, but also the individual (or group) whose perspective the empathizer is attempting to take. I highlight how the emotional needs of others are dynamic and require flexible adaptation and underscore the role of context in appreciating the function of empathy.